Uwagi dotyczące terminologii związanej ze sformalizowanymi systemami zarządzania jakością - Rogala, Piotr (Notes on terminology connected with formalized systems of quality management, 2006)
The article is an attempt of proposing of and systemizing the basic terms connected with the phenomenon which is characterized by the author as the management through the systems of management. The article mentions issues concerning relations between formalized and standardized systems of management. It also presents a classification matrix of management systems, which was designed by the author.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 298-304